The war in the Pasific - FlagTower; First Electronic Publishing Limited ([Boston, Mass.]: FlagTower, 1995)
Explores the political and military history of the 20th century that led Japan to take on the industrial might of the United States and its allies, resulting in defeat for Japan and the dawning of the nuclear era. Includes sound, maps, photographs, video, music, and animation.
System requirements: MPC with 486SX 33MHz processor; 8MB RAM; Windows 3.1 (or later) or Windows 95; 256-color display capability; hard disk with 4MB free space; double-speed CD-ROM drive; mouse; headphones or speakers.
Keywords: World War, 1939-1945 -- Pacific Area -- Software; World War, 1939-1945 -- United States -- Software; World War, 1939-1945 -- Japan -- Software